Jim Dykes interviewed by Martyn Goddard for the Australian response to AIDS oral history project - Dykes, Jim, 1942-1998; Goddard, Martyn; National Library of Australia; Australian Federation of AIDS Organisations (1992)
Reverend Jim Dykes, , speaks about his childhood in Alabama; coming out at 16; becoming involved with the Metropolitan Community Church in 1973; becoming a pastor for MCC; Lanny Dykes; his early awareness of AIDS; moving to Sydney in 1983; AIDS consciousness-raising in Sydney; Community Support Network; Bobby Goldsmith and the Bobby Goldsmith Foundation; establishment and operation of the Ankali Project; effect of HIV/AIDS on society; funerals.
Part of a project undertaken jointly by the Australian Federation of AIDS Organisations and the National Library of Australia focussing on the social and political response in Australia to AIDS.
Recorded in Sydney on 24 June 1992.
Digital master available
Timed summary and transcript (typescript, 65 leaves) available.
Keywords: Dykes, Jim, -- 1942-1998 -- Interviews; Ankali Project; Metropolitan Community Church; Clergy -- Australia -- Interviews; AIDS (Disease) -- Australia; AIDS (Disease) -- Patients -- Care -- Australia; HIV (Viruses) -- Australia